(untitled) - Bloom, A. Martin (Englewood Cliffs, New Jersey, 1969)
The report features examples of policies and partnerships from eight districts whose boards are providing strategic and innovative leadership for after-school programs, and lays out a set of action steps that are easy to follow and readily align with district priorities. Sample school board policies and memoranda of understanding, among other resources, are included.
Keywords: Education, secondary; Evaluation; United States